2023
DOI: 10.1007/s10648-023-09786-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Versus Explanation in Educational Psychology: a Cross-Theoretical Approach to Using Teacher Behaviour to Predict Student Engagement in Physical Education

Abstract: Educational psychology usually focuses on explaining phenomena. As a result, researchers seldom explore how well their models predict the outcomes they care about using best-practice approaches to predictive statistics. In this paper, we focus less on explanation and more on prediction, showing how both are important for advancing the field. We apply predictive models to the role of teachers on student engagement, i.e. the thoughts, attitudes, and behaviours, that translate motivation into progress. We integra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Additionally, the student engagement level in the experimental class was classified as high. The utilization of real-life illustrations in social studies education has been shown to be a successful approach in fostering comprehension and achieving concept mastery (Kassab et al, 2023;Noetel et al, 2023;Yang et al, 2023). The use of this approach enhances student engagement and facilitates comprehension of the offered content.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the student engagement level in the experimental class was classified as high. The utilization of real-life illustrations in social studies education has been shown to be a successful approach in fostering comprehension and achieving concept mastery (Kassab et al, 2023;Noetel et al, 2023;Yang et al, 2023). The use of this approach enhances student engagement and facilitates comprehension of the offered content.…”
Section: Discussionmentioning
confidence: 99%
“…PREDICTING MATH ACHIEVEMENT OVER TIME 9 Recently, there have been a growing number of emerging studies that have utilized machine learning methods to predict achievement outcomes from cognitive and non-cognitive skills, with the goal to better understand important psychological predictors (FİLİZ & Ersoy, 2020;Gamazo & Martínez-Abad, 2020;Kiray et al, 2015;Martinez Abad & Chaparro Caso López, 2017;Nadaf et al, 2021;Nadaf et al, 2023;Noetel et al, 2023;Yoo, 2018). For example, Yoo (2018) conducted an Elastic Net regression analysis to predict Korean 4th graders' math achievement scores with more than 150 predictor variables.…”
Section: Leveraging Machine Learning Methods To Comprehensively Exami...mentioning
confidence: 99%
“…When other constructs are considered, they are often treated as competitors in empirical work designed to test which construct accounts for more variance. This focus on uniqueness and discriminant validity certainly has its place, in that it helps combat construct proliferation and redundancy (Hattie et al, 2020; Noetel et al, 2023). However, it can easily be overemphasized, with the result being a divisiveness and an “us versus them” mentality that bolsters and reinforces the silos (Anderman, 2020; Elliot & Sommet, 2023; Pekrun, 2024).…”
Section: Article Summariesmentioning
confidence: 99%